Affective Interpersonal Touch in Close Relationships: A Cross-Cultural Perspective. (December 2021) - Sorokowska, Agnieszka; Saluja, Supreet; Sorokowski, Piotr; Frąckowiak, Tomasz; Karwowski, Maciej; Aavik, Toivo; Akello, Grace; Alm, Charlotte; Amjad, Naumana; Anjum, Afifa; Asao, Kelly; Atama, Chiemezie S.; et al.
Interpersonal touch behavior differs across cultures, yet no study to date has systematically tested for cultural variation in affective touch, nor examined the factors that might account for this variability. Here, over 14, 000 individuals from 45 countries were asked whether they embraced, stroked, kissed, or hugged their partner, friends, and youngest child during the week preceding the study. We then examined a range of hypothesized individual-level factors (sex, age, parasitic history, conservatism, religiosity, and preferred interpersonal distance) and cultural-level factors (regional temperature, parasite stress, regional conservatism, collectivism, and religiosity) in predicting these affective-touching behaviors. Our results indicate that affective touch was most prevalent in relationships with partners and children, and its diversity was relatively higher in warmer, less conservative, and religious countries, and among younger, female, and liberal people. This research allows for a broad and integrated view of the bases of cross-cultural variability in affective touch.